2002
DOI: 10.1530/eje.0.1460643
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum parathyroid hormone, serum calcium and arterial blood pressure in patients with primary hyperparathyroidism: results of a multivariate analysis

Abstract: Objective: To evaluate the possible relationship between serum calcium, serum parathyroid hormone (PTH) levels and arterial blood pressure (BP) in patients with primary hyperparathyroidism (HPT). Design: A retrospective population-based study. Methods: Charts of 194 patients with proven primary HPT were reviewed, and the main clinical and biochemical parameters were recorded. There were 48 men (24.7%) and 146 women (75.3%), with a median age of 59 years (range 23-82 years). Patients who used antihypertensive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
0
8
0
9
Order By: Relevance
“…Physical examination of patients revealed the presence of hypertension in 78% of patients while its incidence worldwide ranged between 10-40% (22) . After PTX hypertension is either cured or becomes controllable (23) . ECG changes in the form of short QT interval were present in 33% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Physical examination of patients revealed the presence of hypertension in 78% of patients while its incidence worldwide ranged between 10-40% (22) . After PTX hypertension is either cured or becomes controllable (23) . ECG changes in the form of short QT interval were present in 33% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Также следует указать на более частое развитие артериальной гипертензии у больных с первичным гиперапаратиреозом [13][14][15][16][17][18], что подробнее будет рассмотрено ниже.…”
Section: таблицаunclassified
“…По данным разных авторов, частота выявления артериальной гипертензии среди этой группы пациентов варьирует от 10 до 40%, составляя в сред-нем 30% [16]. Отдельные авторы сообщают о более высокой…”
Section: сосудистая стенка и гиперпа-ратиреозunclassified
See 1 more Smart Citation
“…In addition, Kamycheva et al reported that serum PTH predicts coronary heart disease in subjects with calcium levels within the reference range (17). However, the exact role of PTH and/or calcium in the development of CVD is still controversial (19,20).…”
Section: Introductionmentioning
confidence: 99%